Desenvolvimento larval de Eriphia gonagra (Fabricius, 1781) (Decapoda, Xanthidae), em laboratório - Fransozo, Adilson [UNESP] (Sociedade Brasileira de Zoologia, 1987)
The post-embryonic development of the crab from the north coast of São Paulo State, Eriphia gonagra (Fabricius) was studied in laboratory. The experiments were performed in a climatically controlled room at 24±1ºC at a salinity of 36 and the animals were fed with newly hatched Artemia salina nauplii. The larval development of E. gonagra comprises 4 stages of zoea and one megalopa. All larval stages are illustrated and described in detail. The main morphological characters that allow the Identification of the zoeae and megalopae of E. gonagra are analyzed with respect to other Brasilian species of the family Xanthidae.